ASKETISME RELIGI MELALUI PERTENTANGAN TOKOH AJO SIDI DAN HAJI SALEH DALAM CERPEN “ROBOHNYA SURAU KAMI” KARYA AA. NAVIS - Mumtaz, Tsabitah Zain; Rohman, Muh. Fatoni; Vidiyanti, Made Oktavia (Widyaparwa, 2024)
The intensity of worship of Islamic communities in Indonesia is a normal everyday sight. However, some ignore the realities of social life by focusing on their respective deeds of worship. AA writers tried to frame this phenomenon. Navis in a short story entitled Robohnya Surau Kami. The general description of this short story is religiosity with a strong Islamic culture set in Minangkabau. The religious frame that surrounds the short story is contrary to the message the poet wants to convey. To find contradictory meanings, the author analyzes the short story using a qualitative descriptive method with a deconstruction theory approach from Jacques Derrida. The analysis steps are carried out through four stages which include, determining the center and concept of the text (undecidable), dismantling the ideology of the text in binary logic, reversing the metaphysical hierarchy, and neutralizing it by disseminating or spreading meaning. The results obtained from this analysis are that the short story Robohnya Surau Kami contains criticism of religious practices in Indonesia. This criticism regarding religion is an excuse not to work and try in the world. Unlike the title and the atmosphere that is created, it is the misfortune of someone who is devout in worship.Intensitas peribadatan masyarakat Islam di Indonesia menjadi pemandangan wajar sehari-hari. Namun, beberapa mengesampingkan realita kehidupan bermasyarakat dengan memfokuskan diri pada amal ibadah masing-masing. Fenomena ini mencoba dibingkai oleh sastrawan AA. Navis dalam sebuah cerpen berjudul Robohnya Surau Kami. Gambaran umum cerpen ini adalah religiusitas dengan budaya keIslaman yang kental dengan latar tempat Minangkabau. Bingkai religi yang membungkus cerpen bertolak belakang dengan pesan yang ingin disampaikan pengarang. Untuk menemukan makna-makna yang bertolak belakang, penulis menganalisis cerpen menggunakan metode deskriptif kualitatif dengan pendekatan teori dekonstruksi dari Jacques Derrida. Langkah-langkah analisis dilakukan melalui empat tahap yang meliputi, penentuan pusat dan konsep teks (undecidable), pembongkaran ideologi teks dalam logika biner, pembalikan hierarki metafisik, dan penetralisiran dengan diseminasi atau penyebaran makna. Hasil yang didapatkan dari analisis tersebut adalah cerpen Robohnya Surau Kami mengandung kritik terhadap pelaksanaan keagamaan di Indonesia . Kritik tersebut mengenai agama menjadi alasan untuk tidak bekerja dan berusaha di dunia. Tidak seperti judul dan suasana yang dibangun yaitu kemalangan seseorang yang taat beribadah.